2017
DOI: 10.3393/ac.2017.33.5.169
|View full text |Cite
|
Sign up to set email alerts
|

Association of LCT-13910 C/T Polymorphism and Colorectal Cancer

Abstract: PurposeThe activity of epithelial lactase (LCT) is associated with a polymorphism 13910 bp upstream in the lactase encoding gene. Because the association between the LCT-13910 polymorphism and the risk for colorectal cancer is not clear, we investigated the role of the LCT-13910 polymorphism as a potential risk factor for colorectal cancer and colorectal polyps in the Turkish population.MethodsOne hundred sixty-six subjects (74 with polyps, 44 with colorectal cancer, 48 controls), who had undergone a total col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Studies of genetically predicted milk consumption in relation to site-specific cancers are scarce. No association was observed between rs4988235 and colorectal cancer in small case-control studies conducted in Turkey (44 cases and 48 controls) [ 31 ] and Italy (306 cases and 311 controls) [ 32 ]. Lactase persistence was non-significantly positively associated with prostate cancer risk in a meta-analysis of three studies, including a case-control study nested in the European Prospective Investigation into Cancer and Nutrition study (630 cases and 873 controls) and case-control studies of Finnish (1229 cases and 473 controls) and Swedish (2924 cases and 1842 controls) men [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of genetically predicted milk consumption in relation to site-specific cancers are scarce. No association was observed between rs4988235 and colorectal cancer in small case-control studies conducted in Turkey (44 cases and 48 controls) [ 31 ] and Italy (306 cases and 311 controls) [ 32 ]. Lactase persistence was non-significantly positively associated with prostate cancer risk in a meta-analysis of three studies, including a case-control study nested in the European Prospective Investigation into Cancer and Nutrition study (630 cases and 873 controls) and case-control studies of Finnish (1229 cases and 473 controls) and Swedish (2924 cases and 1842 controls) men [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Composed of a glucose and a galactose molecule, lactose is a carbohydrate in mammalian milk [ 14 ]. To allow for uptake by enterocytes in the intestinal wall, lactose is broken down via hydrolysis by the enzyme lactase-phlorizin hydrolase, which is found on the lactase gene ( LCT ) on chromosome 2q21 [ 15 , 16 ]. The hydrolyzed lactose forms glucose and galactose molecules, that can be oxidized to CO2 and H2O or, if under anaerobic conditions, undergo lactic or alcohol fermentation [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the LCT gene is genetically determined, although the activity of the enzyme is always highest in infancy [ 15 ]. In northern European populations, high levels of lactase enzyme can be maintained into adulthood, labeled lactase persistence [ 16 ]. Lactase-phlorizin hydrolase absence or underproduction leads to LI [ 14 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these days in South Korea, despite Koreans having an Asian root, colorectal cancer has been increasing rapidly, as has the consumption of dairy products. Therefore ethnic lineage cannot explain everything [ 13 ].…”
mentioning
confidence: 99%
“…This phenomenon must be investigated further if we are going to be able to determine whether or not it contributes to the initiation and/or development of cancer. Diverse studies, such as the one reported in this article, but with different ethnic characteristics, should be done to determine the factors that contribute to the development of colorectal cancer [ 13 14 ].…”
mentioning
confidence: 99%